'The Impossible Possibility of Love': Reinhold Niebuhr's thought on racial justice. (June 2021) - Hartnett, Liane
Love has been long lauded for its salvific potential in U.S. anti-racist rhetoric. Yet, what does it mean to speak or act in love's name to redress racism? Turning to the work of the North American public intellectual and theologian, Reinhold Niebuhr (1892–1971), this essay explores his contribution to normative theory on love's role in the work of racial justice. Niebuhr was a staunch supporter of civil rights, and many prominent figures of the movement such as James Cone, Jesse Jackson, Martin Luther King Jr., J. Deotis Roberts and Cornel West drew on his theology. Indeed, Niebuhr underscores love's promise and perils in politics, and its potential to respond to racism via the work of critique, compassion, and coercion. Engaging with Niebuhr's theology on love and justice, then, not only helps us recover a rich realist resource on racism, but also an ethic of realism as antiracism.